2015
DOI: 10.1111/anae.13306
|View full text |Cite
|
Sign up to set email alerts
|

Preventing chronic postoperative pain

Abstract: Summary Chronic postoperative pain is common. Nerve injury and inflammation promote chronic pain, the risk of which is influenced by patient factors, including psychological characteristics. Interventional trials to prevent chronic postoperative pain have been underpowered with inadequate patient follow‐up. Ketamine may reduce chronic postoperative pain, although the optimum treatment duration and dose for different operations have yet to be identified. The evidence for gabapentin and pregabalin is encouraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 69 publications
2
58
0
5
Order By: Relevance
“…As such, the physiological transduction and transmission of noxious stimuli are a vital protective mechanism, allowing withdrawal from potential damage by environmental factors. However, if this pain is not managed effectively, it may become chronic pain, harming the related organs and leading to dysfunction [10,11].…”
Section: Y H Gao and Cw LI Contributed Equally To This Workmentioning
confidence: 99%
“…As such, the physiological transduction and transmission of noxious stimuli are a vital protective mechanism, allowing withdrawal from potential damage by environmental factors. However, if this pain is not managed effectively, it may become chronic pain, harming the related organs and leading to dysfunction [10,11].…”
Section: Y H Gao and Cw LI Contributed Equally To This Workmentioning
confidence: 99%
“…However, the results were only found in the disc herniation group. A possible reason for the different results for patients with disc herniation may be the presence of inflammation, which often causes more on-going nociceptive stimuli and constant pain experience that could cause more risk of plasticity changes in the nervous system [6]. In disc herniation, the sciatic pain is described to have both a neuropathic component with the mechanical-stimuli causing the nerve root compression and also an inflammatory component [19].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic, clinical, work-related and psychological risk factors may partly explain poor outcomes after spinal surgery [5]. Another reported risk factor is insufficient pain treatment pre-and post-surgery [6]. It has been suggested that screening of somatosensory function may contribute to the understanding of pain mechanisms involved [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kerusakan dan inflamasi pada nervus akan memicu rasa nyeri. Rasa nyeri pasien dipengaruhi oleh berbagai faktor, termasuk psikologi dari pasien (Reddi, 2016). Menurut Yin et al (2015), 80% pasien paska operasi mengalami nyeri dan menurut Kable et al (2004), 41 % pasien paska operasi masih merasakan nyeri meskipun sudah pulang ke rumah dan 20 % merupakan pasien yang mengalami pembedahan TURP.…”
Section: Trans Urethral Resection Of Theunclassified